Effect of care environment on educational attainment among orphaned and separated children and adolescents in Western Kenya - Dorothy Apedaile; Allison DeLong; Edwin Sang; David Ayuku; Lukoye Atwoli; Omar Galárraga; Paula Braitstein (BMC, 2022)
Abstract Background There are approximately 140 million orphaned and separated children (OSCA) around the world. In Kenya, many of these children live with extended family while others live in institutions. Despite evidence that orphans are less likely to be enrolled in school than non-orphans, there is little evidence regarding the role of care environment. This evidence is vital for designing programs and policies that promote access to education for orphans, which is not only their human right but also an important social determinant of health. The purpose of this study was to compare educational attainment among OSCA living in Charitable Children's Institutions and family-based settings in Uasin Gishu County, Kenya. Methods This study analyses follow up data from a cohort of OSCA living in 300 randomly selected households and 17 institutions. We used Poisson regression to estimate the effect of care environment on primary school completion among participants age ≥ 14 as well as full and partial secondary school completion among participants age ≥ 18. Risk ratios and 95% confidence intervals were estimated using a bootstrap method with 1000 replications. Results The analysis included 1406 participants (495 from institutions, 911 from family-based settings). At baseline, 50% were female, the average age was 9.5 years, 54% were double orphans, and 3% were HIV-positive. At follow-up, 76% of participants age ≥ 14 had completed primary school and 32% of participants age ≥ 18 had completed secondary school. Children living in institutions were significantly more likely to complete primary school (aRR: 1.18, 95% CI: 1.10-1.28) and at least 1 year of secondary school (aRR: 1.28, 95% CI: 1.18-1.39) than children in family-based settings. Children living in institutions were less likely to have completed all 4 years secondary school (aRR: 0.79, 95% CI: 0.43-1.18) than children in family-based settings. Conclusion Children living in institutional environments were more likely to complete primary school and some secondary school than children living in family-based care. Further support is needed for all orphans to improve primary and secondary school completion. Policies that require orphans to leave institution environments upon their eighteenth birthday may be preventing these youth from completing secondary school.